2017
DOI: 10.1186/s12876-017-0609-6
|View full text |Cite
|
Sign up to set email alerts
|

The inverse effect of meal intake on controlled attenuation parameter and liver stiffness as assessed by transient elastography

Abstract: BackgroundControlled attenuation parameter (CAP) and liver stiffness (LS) measured by transient elastography (TE, Fibroscan®) have been used for steatosis and fibrosis assessment. We evaluated the effect of meal intake on CAP and LS values.MethodsForty patients who had had a liver biopsy within the previous month were recruited. The biopsy was graded for fibrosis (F) and steatosis (S) stagings. TE was performed after overnight fasting (baseline values) and 15, 30, 45, 60, 90, and 120 min following the intake o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 20 publications
3
25
1
Order By: Relevance
“…We have not found the same effect of meal intake on CAP values. In our study, the timing of the measurements was set at 30 min after meal ingestion, while in the study by Ratchatasettakul et al [20], the CAP post-meal peak was observed 60 min after meal intake. Our time point was chosen according to previous observations indicating that postprandial hyperemia and the postprandial increase of portal pressure were highest 30 min after meal ingestion [18].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have not found the same effect of meal intake on CAP values. In our study, the timing of the measurements was set at 30 min after meal ingestion, while in the study by Ratchatasettakul et al [20], the CAP post-meal peak was observed 60 min after meal intake. Our time point was chosen according to previous observations indicating that postprandial hyperemia and the postprandial increase of portal pressure were highest 30 min after meal ingestion [18].…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Ratchatasettakul et al [20], a significant decline of CAP values following meal intake was observed at 15–120 min. We have not found the same effect of meal intake on CAP values.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations